Synthesis of Some New Polysiloxane Ligands Systems (Glycinate)-Part II† - EL-Nahhal, L.M.; EL-Kurd, H.M.; Parish, R.V. (Asian Journal of Chemistry, 2010)
Polysiloxane-immobilized glycinate chelating ligands system of the general formula Ⓟ-(CH2)3NHCH2CO2H (where Ⓟ represents the polysiloxane network) have been prepared by two methods. The first used is through the reaction between 3-amino-propyltriethoxysilane and chloroethylacetate, ClCH2COOEt, followed by hydrolytic polycondensation with tetraethoxysilane (before polymerization). The second method, which was used, is through the reaction of 3-aminopropylpolysiloxane and haloethylacetate XCH2COOEt, X = Cl or I (after polymerization). The elemental analysis indicates that more glycinate ligand groups were obtained by functionalization before polymerization than after polymerization process. The glycinate polysiloxane ligands show high potential for copper ion uptake.